Rational expectations and inflation targeting: An analysis for ten countries - Pia Fromlet (Uppsala University, Department of Economics, 2010)
In this paper I evaluate inflation targeting for ten countries. The evaluation is based on unconditional as well as conditional measures of the variance of inflation around target. With strict inflation targeting, expectations of the future deviation from target given information about the deviation from the target today should be equal to zero. Using the Consumer Price Index (CPI) when calculating the inflation rate, I find that the null hypothesis can be rejected for six of ten countries. In an extended approach I add lagged output gap as an information variable for countries where data was available. I then get the result that rational expectations and strict inflation targeting can be rejected for five countries. Out of the ten countries, the United Kingdom has conducted inflation targeting most in line with the theory of rational expectations and strict inflation targeting, and Poland the least.
urn:nbn:se:uu:diva-131113
Keywords: E31; E52; E58; 330; inflation targeting; rational expectations; monetary policy; Inflationssteuerung; Rationale Erwartung; Geldpolitik; Verbraucherpreisindex; Welt